Associations of Serum Fluorescent Advanced Glycation End Products, Glycemic Control, Vascular Complications and Duration of Diabetes Mellitus - Nivedita L. Rao; Greeshma B. Kotian; Shaheena Yasser (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Introduction: Advanced glycation end products (AGEs), glycemic control and diabetes duration, all have roles in the development of vascular complications that are associated with morbidity and mortality in diabetic patients. Understanding the associations between serum fluorescence of advanced glycation end products, glycemic control, microvascular complications and duration of diabetes mellitus therefore, becomes vital. Significantly higher serum fluorescence of AGEs and higher incidence of microvascular complications have been found in diabetic patients of higher age with poorer glycemic control and longer diabetes duration. Poor glycemic control was associated with disease duration, hypercholesterolemia, high level of low density lipoprotein, hypertension and income level of the patients. Significant positive correlations have been found between serum fluorescence of AGEs, duration of diabetes mellitus, glycated haemoglobin and fasting glucose levels. Observations made from key study findings indicate that intensive glycemic control and therapeutic strategies that target molecular mechanisms involving AGEs are warranted in older patients with longer diabetes duration who are at higher risk of developing diabetic microvascular complications.